2-Arachidonoylglycerol as an Endogenous Cue Negatively Regulates Attachment of the Mussel Perna viridis - Dai, Qi; Wang, Zhi-Xuan; Sheng, Yan-Qing; Wu, Zhi-Wen; Qiu, Yan; Su, Pei; Ke, Cai-Huan; Feng, Dan-Qing (Frontiers in Marine Science, 2021)
Endocannabinoids play important roles in the functioning of various physiological systems in humans and non-mammalian animals, including invertebrates. However, information concerning their roles in physiological functions in members of the phylum Mollusca is scarce. Here the hypothesis that the endocannabinoids are involved in mediating settlement of marine invertebrates was tested. Two endocannabinoids (N-arachidonoyl ethanolamide [AEA] and 2-arachidonoyl glycerol [2-AG]), and two endocannabinoid-like lipids (N-Oleoylethanolamide [OEA] and N-Palmitoylethanolamide [PEA]) were detected in the green mussel Perna viridis. In particular, 2-AG was present at significantly higher levels in unattached P. viridis compared with attached mussels. The in vivo level of 2-AG was inversely correlated with the attachment activity of P. viridis. Furthermore, exposure to synthetic 2-AG inhibited attachment of P. viridis in a reversible manner. Transcriptomic analysis suggested that up-regulation of 2-AG synthase (Phospholipase C-β, PLC-β) and down-regulation of its degrading enzyme (Monoacylglycerol lipase, MAGL) resulted in higher levels of 2-AG in unattached mussels. A putative mechanism for the negative regulation of mussel attachment by 2-AG is proposed that involves a Ca2+- Nitric oxide (NO)- cyclic guanosine monophosphate (cGMP) pathway. This study broadens our understanding of the evolution and roles of the endocannabinoid system in animals, and reveals an endogenous regulatory cue for mussel attachment.